Determination of stability constants of complexes of neutral analytes with charged cyclodextrins by affinity capillary electrophoresis - Beneš, Martin; Zusková, Iva; Svobodová, Jana; Gaš, Bohuslav (Electrophoresis, 2012)
A novel procedure for the determination of stability constants in systems with neutral analytes and charged complexation agents by affinity capillary electrophoresis was established. This procedure involves all necessary corrections to achieve precise and reliable data. Temperature, ionic strength, and viscosity corrections were applied. Based on the conductivity measurements, the average temperature of the background electrolyte in the capillary was kept at the constant value of 25°C by decreasing the temperature of the cooling medium. The viscosity correction was performed using the viscosity ratio determined by an external viscosimeter. The electrophoretical measurements were performed, at first, at constant ionic strength. In this case, the increase of ionic strength caused by increasing complexation agent concentration was compensated by changing of the running buffer concentration. Subsequently the dependence of the analyte effective mobility on the complexation agent concentration was measured without the ionic strength compensation (at variable ionic strength). The new procedure for determination of the stability constants even from such data was established. These stability constants are in a very good agreement with those obtained at the constant ionic strength. The established procedure was applied for determination of the thermodynamic stability constants of (R, R)-(+)- and (S, S)-(-)-hydrobenzoin and R- and S-(3-bromo-2-methylpropan-1-ol) complexing with 6-monodeoxy-6-mono(3-hydroxy)propylamino-β-cyclodextrin hydrochloride.
Keywords: chemické modely; beta-Cyclodextrins; Thermodynamics; elektroforéza kapilární; Electrophoresis, Capillary; Viscosity; lineární modely; beta-cyklodextriny; Linear Models; Osmolar Concentration; viskozita; osmolární koncentrace; termodynamika; Models, Chemical